E-learning readiness of teachers in the new normal education: The case of national high schools in Eastern Samar - Rovinson Deladia Gaganao; Rey Naranja Discar; Ilyich Nicolai Lenin Fabillar (International Journal of Evaluation and Research in Education (IJERE), 2022)
Online learning readiness assessment allows for the comprehensive planning of online learning strategies. Therefore, this study was conducted to examine the readiness of 207 national high school instructors in the southern part of Eastern Samar for online learning in the new normal education. The study used a descriptive-comparative research plan and a survey questionnaire for data collection. The study found that teachers were ready to implement e-learning. Specifically, teachers are ready in terms of technical skills, attitude toward online learning, as well as time management and time commitment, but only somewhat prepared in terms of experience with online learning and teaching. It is recommended that teachers participate in different training, workshops, and seminars related to e-learning to gain more online learning and teaching experience and fully prepare for e-learning implementation.